Impact of Central Bank Digital Currencies (CBDCs) on Monetary Policy Transmission Mechanisms: Evidence from Recent Global Implementations - Yusuf, Jamiu Adeniyi (Buhalterinės apskaitos teorija ir praktika, 2025)
Central Bank Digital Currencies (CBDCs) represent a transformational evolution in financial systems with profound implications for monetary policy transmission, particularly in developing economies. Focusing on conventional channels like interest rates, credit supply, and exchange rates, this study examines how the implementation of a CBDC influences the transmission mechanisms of monetary policy in Nigeria. An approach incorporating Dynamic Stochastic General Equilibrium (DSGE) modelling with Vector Error Correction (VECM) was adopted. Macroeconomic data from the National Bureau of Statistics and the Central Bank of Nigeria were used to calibrate the models. MATLAB/Dynare was used for policy simulations, and EViews was used to assess the dynamic responses of key macroeconomic parameters with and without CBDCs. Macroeconomic data from the National Bureau of Statistics and the Central Bank of Nigeria were used to calibrate the models. MATLAB/Dynare and EViews were used to simulate policy responses and assess the dynamic behaviour of key macroeconomic parameters in both CBDC and non-CBDC scenarios. The results indicate that CBDC issuance exhibits strong persistence and is primarily driven by liquidity conditions and inflation dynamics, while the conventional interest rate channel plays a limited role in the short run. The findings suggest that CBDC adoption reorders existing monetary transmission mechanisms rather than replacing them. CBDCs may improve monetary policy effectiveness if created and deployed with adequate regulatory protections and stakeholder involvement. To reduce transitional risks, a phased approach backed by strong legal and institutional infrastructures is needed.
Keywords: Central Bank Digital Currency (CBDC); Monetary Policy Transmission; Financial Stability; Interest Rate Channel